2017
DOI: 10.1093/mmy/myx128
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow–derived mesenchymal stem cells transplantation alters the course of experimental paracoccidioidomycosis by exacerbating the chronic pulmonary inflammatory response

Abstract: Several studies have shown the potential use of bone marrow mesenchymal stem cells (BM-MSCs) as a therapeutic approach to infectious diseases. Since BM-MSCs can exert antimicrobial properties and influence the immune response against pathogens, our aim was to study the antimicrobial therapeutic potential of BM-MSCs in an experimental model of paracoccidioidomycosis (PCM). BM-MSCs were isolated from BALB/c donor mice. Paracoccidioides brasiliensis-infected male BALB/c mice were injected with purified BM-MSCs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…They may interact with host cells and establish the colonisation and dissemination of fungi in the host organism, (17,41) interacting with components of the host extracellular matrix (ECM) and lung cells. (41) Most adhesins are enzymes of the glycolytic pathway, tricarboxylic acid (TCA), and glyoxylate cycle of Paracoccidioides spp. They have adhesive properties that facilitate the interaction with the host ECM and act as 'moonlighting' proteins.…”
Section: Discussionmentioning
confidence: 99%
“…They may interact with host cells and establish the colonisation and dissemination of fungi in the host organism, (17,41) interacting with components of the host extracellular matrix (ECM) and lung cells. (41) Most adhesins are enzymes of the glycolytic pathway, tricarboxylic acid (TCA), and glyoxylate cycle of Paracoccidioides spp. They have adhesive properties that facilitate the interaction with the host ECM and act as 'moonlighting' proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of PGE 2 levels indirectly enhanced the immune response, leading to higher bacterial clearance[ 26 , 83 ]. Further, injection of BM-MSCs in Paracoccidioides brasiliensis -infected mice led to increased fungal levels and exaggerated immune responses, with increased accumulation of neutrophils, eosinophils, and M2 macrophages, leading to congestion and edema in lungs[ 84 ]. Similarly, treatment with BM-MSCs in mice with latent M. bovis infection resulted in significantly higher mycobacterial number and granuloma formation[ 85 ].…”
Section: Mscs In Immunomodulationmentioning
confidence: 99%
“…In a previously conducted study on COVID-19 patients, injection of MSCs to lungs in pulmonary disease showed a protective effect on the endothelial cells ( Liang et al, 2020 ). In another study published recently, it is quoted that MSC transplantation significantly reduced neutrophil-mediated inflammation of the airways by inhibiting the Th17 signaling pathway in a mouse model of asthma triggered by the fungus Aspergillus fumigatus hyphal extract ( Arango et al, 2018 ). Bone marrow–derived MSCs show an immunomodulatory effect on macrophages stimulated by Aspergillus fumigatus conidia that further lowers the expression of tumor necrosis factor-α (TNF-α) and increases the expression of IL-10 ( Arango et al, 2018 ).…”
Section: Msc-based Management Of Covid-19–associated Mucormycosismentioning
confidence: 99%